Sosialisasi Digital Marketing dalam Upaya Peningkatan Penjualan Produk UMKM di Kepulauan Banda, Maluku Tengah - Radianto, Amelia Josefien Viotty; Laitupa, Muhammad Fadila; Leatemia, Senda Yunita; Anakotta, Fanny Monica; Fauzan S, M Rifkhi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The purpose of this community service activity is to provide education in the form of outreach to increase sales of MSME products through digital marketing in the Banda Islands, Central Maluku. The methods used to carry out community service activities are qualitative methods in the form of interviews and active and participatory learning methods. After being evaluated through several interview questions, this socialization was able to increase the knowledge and insight of MSME players in the Banda Islands so that they could maximize the potential of technology around them in an effort to increase sales of MSME products.